WHO KILLED BARCELONA'S HIGH SPEED STATION PROMISES ? INFRASTRUCTURE POLITICAL CAPTURE, SCALING NARRATIVES AND THE URBAN FABRIC - Nacima BARON (European Journal of Geography)
The paper explores the economics and politics of megaproject failure in Spain. Taking Barcelona's high-speed station as a case study, it demonstrates that, rather than a victim of austerity policies, this project was much more the hostage of a struggle between national, regional and city scales, representations and policy narratives. After introducing the debate on the promise and disillusionment around high-speed stations, the discussion highlightsthree stages in the project timeline. It shows the station’s unstable position in high speed network planning from the early 90s to the 2000s. It describes the competing geostrategic perspectives between Madrid and Catalonia that halted the project during the 2008-2014 crisis. And it recounts how, since 2015, local stakeholders have reaffirmed their commitment to the completion of the station, but have failed to integrate it with new trends and processes of urban renovation.